Immunohistochemical Characterization of Apoptotic and Macrophage Reactions in The Thyroid Gland Under Microelement Deficiency - Aslonov, O. G. (American Journal of Biomedicine and Pharmacy, 2026)
The study evaluates apoptotic activity and macrophage response in thyroid tissue under combined microelement deficiency (Mg, Fe, Se, Zn) using CD95 and CD163 markers in white outbred rats. Microelement deficiency was associated with increased CD95 expression, indicating enhanced apoptosis in thyrocytes, and elevated CD163 expression, reflecting activation of M2 macrophages and tissue remodeling. These changes demonstrate structural and functional alterations in the thyroid gland linked to increased cell death and immune reorganization.